Writing the future. Issue 4 (2nd October 2019) - Garcia, Edgar
ABSTRACT: In Plato's dialogues, theories of the sign emerge from theories about divination. Language and its arts are intertwined with the becoming-conscious contradictions of fortune-telling. This essay investigates the poetics of fortune-telling to examine what Plato banishes from his philosophical system: the political, philosophical and aesthetic amalgams of the future in our everyday, often future-less lives.